COMPONENT AND FUNCTION OF SPEECH ACT IN THE TRANSLATION OF MIRROR IMAGE INTO BELAHAN JIWA - I Kadek Restu Sumaranama (Program Magister Linguistik Universitas Udayana, 2015)
This study was intended to examine the components of speech act consisting of locutionary act, illocutionary act and perlocutionary act and to analyze the classification of communicative illocutionary acts and functions of speech act both in source language and target language. The data were collected from the novel entitled Mirror Image (Steel:1999) and its Indonesian translated version entitled Belahan Jiwa (Sigarlaki:2001). The results showed that there were some changes of locutionary act type of utterance that occurred in the translation, consisting of change in source langauge declarative form into target language interrogative form, from source language declarative form into target language imperative form, from source language interrogative form into target language imperative form and from source language imperative form into target language declarative form. The change in utterance types from the level of locutionary act into illocutionary act occurred from source language to target language. In the locutionary act, the force was only focused on the surface of the utterance form, when the utterance was brought into the illucotionary level, the involvement of the speaker’s intention was added to the virtue or context of the utterance. The changes involved the ones from source language declarative into acknowledgment type of source language illocutionary with accept function, from source language interrogative into target language directive type of illocutionary with question function. The second one, the changes occurred from source language declarative into source language constantive type of illocutionary with informative function, from target language imperative into source language directive type of illocutionary with requestive function. The third one was the changes from source language interrogative into target language imperative which was classified into directive type of illocutionary with requirement function in both source language and target language. And the last one, the changes from source language imperative into directive type of illocutionary with source language requestitive function, from target language declarative into target language constantive type of illocutionary with assertive function. This study expected to contribute significantly to the use of speech act approach in translation activities.